Genetic Variation among Open Pollinated Progenies of Melia azedarach under Nursery and Field Conditions - Dhillon, G. P. S.; Sidhu, D. S.; Singh, B.; Singh, A. (Indian Forester, 2009)
The present study was conducted at Punjab Agricultural University, Ludhiana (Punjab) by raising 11 progenies of plus trees of Melia azedarach under nursery and field conditions. The differences among progenies for collar diameter and plant height were significant at nursery stage. The plant height and diameter at age of 1, 3.5, 5 and 7 year also varied significantly among progenies. The heritability was observed to be medium for diameter (40.76 to 85.08 %) and height (52.07 to 76.25 %). The genetic gain and variation coefficients for diameter were also relatively higher under field conditions. The results indicated good potential for improvement for growth traits by collecting seeds from plus trees or seed orchards.